Comparative Study of Desktop-Based Antivirus Application Adoption Rate - Baharuddin Mustahir, Julianto Mansa, Gabriel Tamboto (JR Education, 2021)
Antivirus is a type of software that is used to secure, detect, and remove computer viruses from computer systems. Antivirus can be an application program that functions to detect and clean malicious programs. The purpose of this study was to measure the level of acceptance of antivirus programs running on desktop devices. In addition, it is expected to be able to apply and distinguish the performance of the 2 antiviruses for the identification, cleaning and deletion of a virus-infected file. The method used to determine the level of acceptance of an anti-virus is using the TAM acceptance model. The results of this study indicate that the majority of users have been able to use antivirus properly and will continue to use it in the future. The results of this study recommend that for desktop-based computer security processes it is better to use a trusted antivirus so that the computer security process becomes more effectively guaranteed.